Preparation method of high-performance composite binder for graphite negative electrode
The composite adhesive prepared by mixing LiPAA solution, thickening solution, sodium hyaluronate solution and SBR emulsion, the problem of the graphite negative electrode adhesive of lithium battery is easily broken and fall off after multiple charges and discharges, and the preparation of high-performance composite adhesive is realized, improving the adhesiveness and mechanical properties of the electrodes, and enhancing the ionic conductivity.
Patent Information
- Application Number
- CN202411814413.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-11
- Publication Date
- 2025-03-04
AI Technical Summary
The binder of the graphite negative electrode of the existing lithium battery is prone to cracking and falling off after multiple charges and discharges, resulting in a decrease in capacity retention rate. The existing composite binder has defects of low viscosity, high hardness and high brittleness, which cannot meet the requirements of the battery industry.
Using a high-performance composite adhesive for graphite negative electrode, a composite adhesive with good adhesiveness and mechanical properties is obtained by stirring and mixing LiPAA solution, thickening solution, sodium hyaluronate solution and SBR emulsion.
It improves the adhesiveness and mechanical properties of the electrode, enhances ionic conductivity, reduces resistance, increases the current circulation, and extends the service life of the electrode.
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of lithium ion batteries, in particular to a method for preparing a high-performance composite binder for a graphite negative electrode. Background Art
[0002] Lithium batteries are closely related to people's lives. As one of the important components of batteries, the quality of electrodes is of great significance. Electrodes are generally composed of active materials, binders, conductive agents, current collectors, etc., and the binder, as an intermediate connecting various substances, has an important influence on maintaining the integrity of the electrode and building the transmission channels of ions and electrons. In addition to having the characteristics of good bonding performance, high tensile strength, good flexibility and low Young's modulus that ordinary binders also have, high-performance binders used for electrodes must also have good stability and ionic conductivity.
[0003] In the prior art, the most commonly used negative electrode for lithium electrons is a graphite electrode, which generally uses a binder made of a CMC-SBR system. However, the prepared electrode electrolyte has low wettability, high resistance, and low ionic conductivity. Moreover, after multiple charge and discharge processes, graphite particles are still prone to cracking and falling off, which reduces the capacity retention rate and cannot meet existing needs. Therefore, composite binders have gradually emerged. For example, lithium polyacrylate (LiPAA) has good ionic conductivity and has begun to be used as a new type of water-based binder for the preparation of electrode composite adhesives, which has good application prospects. However, lithium polyacrylate has the defects of low viscosity, high hardness, and high brittleness, which cannot meet the requirements for binders in battery industrial production.
[0004] In summary, it is of great significance to solve the above problems and provide a method for preparing a high-performance adhesive with good adhesion and mechanical properties and good ionic conductivity. Summary of the invention
[0005] The purpose of the present invention is to provide a method for preparing a high-performance composite binder for a graphite negative electrode, so as to solve the problems raised in the prior art.
[0006] To achieve the above object, the present invention provides the following technical solutions: A method for preparing a high-performance composite binder for a graphite negative electrode comprises the following steps: stirring and mixing a LiPAA solution, a thickening solution, a sodium hyaluronate solution, and an SBR emulsion to obtain a composite binder.
[0007] Preferably, the composite binder comprises the following raw materials, based on 100 parts by mass: 20-50 parts of LiPAA solution, 20-40 parts of thickening solution, 10-20 parts of sodium hyaluronate solution, and the rest is SBR emulsion.
[0008] Preferably, the content of lithium polyacrylate in the LiPAA solution is 3.8-4.2wt%; the content of thickener in the thickener thickening solution is 1.8-2.2wt%; the content of sodium hyaluronate in the sodium hyaluronate solution is 1.8-2.2wt%; and the content of effective substances in the SBR emulsion is 46-50wt%.
[0009] Preferably, the thickener in the thickening solution includes one of sodium carboxymethyl cellulose and xanthan gum; and the effective substance in the SBR emulsion is styrene-butadiene rubber.
[0010] Preferably, during the stirring and mixing process, the rotation speed is 350-450 r / min and the time is 11-13 h.
[0011] Preferably, the method for preparing lithium polyacrylate in the LiPAA solution comprises the following steps: (1) Add acrylic acid to anhydrous ethanol, stir evenly, add 1,4,8,11-tetrakis(carbamoylmethyl)-1,4,8,11-tetraazacyclotetradecane and an activator, stir at 60-70°C for 4-5 hours, purify, evaporate and concentrate, and dry to obtain modified acrylic acid; (2) Add modified acrylic acid, lithium acrylate and vinyl ethylene carbonate to methanol and stir evenly, add azobisisobutyronitrile, introduce nitrogen and stir at 80-95°C for 20-24 hours, filter, wash and dry to obtain lithium polyacrylate.
[0012] Among them, in the modified acrylic acid, the mass ratio of acrylic acid, 1,4,8,11-tetrakis(carbamoylmethyl)-1,4,8,11-tetraazacyclotetradecane, and activator is 1:1.5~1.8:2.5~3; in the lithium polyacrylate, the mass ratio of modified acrylic acid, lithium acrylate, vinyl ethylene carbonate, and azobisisobutyronitrile is 1:7~8:0.4~0.5:0.08~0.1.
[0013] Preferably, the preparation method of the SBR emulsion comprises the following steps: (1) adding styrene-butadiene rubber to deionized water and stirring evenly, adding peracetic acid, stirring at 25-30° C. for 1-2 hours, purifying, washing, and drying to obtain epoxidized styrene-butadiene rubber; (2) adding epoxidized styrene-butadiene rubber into a reaction kettle and stirring evenly, adding 2,4-aminopyrimidine-5-carboxylic acid and trifluoroacetic acid, stirring at 80-90° C. for 1.5-2 h under microwave conditions of 200-250 W, and purifying to obtain active styrene-butadiene rubber; (3) Adding active styrene-butadiene rubber to deionized water and stirring evenly, adding amino-tetraethylene glycol-carboxylic acid and an activator, stirring at 50-60° C. for 7-8 hours, and obtaining modified styrene-butadiene rubber; (4) Add modified styrene-butadiene rubber and Tween 80 into deionized water for ultrasonic dispersion and shear dispersion to obtain SBR emulsion.
[0014] The epoxidized styrene-butadiene rubber comprises the following raw materials in parts by mass: 33-35 parts of styrene-butadiene rubber, 95-100 parts of deionized water, and 8-12 parts of peracetic acid; the active styrene-butadiene rubber comprises the following raw materials in parts by mass: 13-15 parts of epoxidized styrene-butadiene rubber, 13-16 parts of 2,4-aminopyrimidine-5-carboxylic acid, and 5-6 parts of trifluoroacetic acid; the modified styrene-butadiene rubber comprises the following raw materials in parts by mass: 15-17 parts of active styrene-butadiene, 8-10 parts of amino-tetraethylene glycol-carboxylic acid, and 7-9 parts of activator; in the SBR emulsion, the mass ratio of the modified styrene-butadiene rubber to Tween 80 is 4:0.4-0.5.
[0015] Preferably, the activator is 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide and N-hydroxysuccinimide in a mass ratio of 1:1 to 1.5.
[0016] Compared with the prior art, the present invention has the following beneficial effects: (1) Polymerized lithium acrylate is a water-soluble polymer with good dispersibility in water. It has a large number of lithium acetate groups, which can form a bridge between the electrolyte and the electrode active material, promote the transmission of lithium ions, and thus show good conductivity. The present invention adds a thickening solution containing sodium carboxymethyl cellulose or xanthan gum to the composite adhesive. It is a polysaccharide molecule with rich hydroxyl functional groups, which is easy to form intermolecular hydrogen bonds with the carboxyl functional group structure in polymerized lithium acrylate, greatly improving the bonding performance of polymerized lithium acrylate. On the one hand, the added sodium hyaluronate contains a large number of hydroxyl groups, which improves the bonding force. On the other hand, sodium hyaluronate has good elasticity and helps to absorb mechanical stress. Since the negative electrode is easy to expand during the power-on process, sodium hyaluronate can reduce the stress caused by volume expansion, thereby improving the toughness of the electrode.
[0017] (2) In order to further improve the wettability of the electrode and electrolyte added with the composite binder, the present invention also modifies acrylic acid, grafts it with 1,4,8,11-tetrakis(aminocarbonylmethyl)-1,4,8,11-tetraazacyclotetradecane, and then copolymerizes it with lithium acrylate. Such a tetraazacyclic structure helps lithium acrylate to form a branched structure during polymerization, which can further improve its mechanical properties compared with linear polymerization. At the same time, vinyl ethylene carbonate is introduced to participate in the copolymerization, so that the polymerized lithium acrylate has a large amount of vinyl ethylene carbonate structure, which can improve the compatibility with the electrolyte, has high wettability, helps to reduce resistance, increase current circulation, and improve ionic conductivity, thereby further improving the conductive performance.
[0018] (3) The present invention modifies a portion of styrene-butadiene rubber into epoxidized styrene-butadiene rubber for modification and grafting, introduces hydroxyl, carboxyl, and amino active groups on its surface, thereby increasing the number of hydrogen bonds formed with polysaccharides to improve mechanical properties, introduces hydrophilic segments, and improves its dispersibility in adhesives; at the same time, the present invention reduces the double bond content on the styrene-butadiene rubber segment during the grafting process, which can improve stability, reduce oxidation, and improve durability, and compensates for the reduced adhesion to the current collector copper foil caused by the reduction of double bonds through the polyamino structure. The introduced pyrimidine structure also helps to improve the conductive properties, thereby obtaining a high-performance composite adhesive. DETAILED DESCRIPTION
[0019] Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in the field without making any creative work shall fall within the scope of protection of the present invention.
[0020] It should be noted that there is no special restriction on the purchase manufacturers of all the raw materials involved in the present invention, which exemplarily include: LiPAA solution, SBR emulsion, and conductive carbon black are provided by Kelude New Energy Technology Co., Ltd.; sodium carboxymethyl cellulose; sodium hyaluronate; xanthan gum; 1,4,8,11-tetrakis(carbamoylmethyl)-1,4,8,11-tetraazacyclotetradecane, CAS: 345612-63-7; lithium acrylate; vinyl ethylene carbonate, CAS: 4427-96-7; styrene-butadiene rubber, molecular weight of 1000~2000; 2,4-aminopyrimidine-5-carboxylic acid, CAS: 18588-61-9; amino-tetraethylene glycol-carboxylic acid, CAS: 134978-99-7.
[0021] In the following examples, parts are by mass, and the raw materials are all commercially available. The preparation of the relevant solutions in Examples 1 to 5 and Comparative Examples 1 to 3 is as follows: The content of lithium polyacrylate in the LiPAA solution is 4wt%; the content of effective substances in the SBR emulsion is 48wt%; the preparation method of the sodium carboxymethyl cellulose solution comprises the following steps: adding 1g of sodium carboxymethyl cellulose to 51g of deionized water and stirring evenly to obtain a sodium carboxymethyl cellulose solution with a sodium carboxymethyl cellulose content of 2wt%; the preparation method of the sodium hyaluronate solution comprises the following steps: adding 0.2g of sodium hyaluronate to 9.8g of deionized water and stirring evenly to obtain a sodium hyaluronate solution with a sodium hyaluronate content of 2%; the preparation method of the xanthan gum solution comprises the following steps: adding 0.2g of xanthan gum to 9.8g of deionized water and stirring evenly to obtain a xanthan gum solution with a xanthan gum content of 2%.
[0022] Example 1: LiPAA solution, sodium carboxymethyl cellulose solution, sodium hyaluronate solution and SBR emulsion were mixed in a mass ratio of 4:4:1:1, and stirred at 350 r / min for 12 h to obtain a composite binder.
[0023] Example 2: LiPAA solution, sodium carboxymethyl cellulose solution, sodium hyaluronate solution and SBR emulsion were mixed in a mass ratio of 5:3:1:1 and stirred at 350 r / min for 12 h to obtain a composite binder.
[0024] Example 3: LiPAA solution, sodium carboxymethyl cellulose solution, sodium hyaluronate solution and SBR emulsion were mixed in a mass ratio of 2:2:2:2 and stirred at 350 r / min for 12 h to obtain a composite binder.
[0025] Example 4: LiPAA solution, xanthan gum solution, sodium hyaluronate solution and SBR emulsion were mixed in a mass ratio of 4:4:1:1, and stirred at 350 r / min for 12 h to obtain a composite adhesive.
[0026] Example 5: LiPAA solution, xanthan gum solution, sodium hyaluronate solution and SBR emulsion were mixed in a mass ratio of 2:2:2:2, and stirred at 350 r / min for 12 h to obtain a composite adhesive.
[0027] Comparative Example 1: Based on Example 1, the existing commercial adhesive CMC-SBR is used, and the other processes remain unchanged, specifically as follows: sodium carboxymethyl cellulose solution and styrene-butadiene rubber emulsion are mixed in a mass ratio of 1:1, and stirred at 300 r / min for 6 hours to obtain a composite adhesive.
[0028] Comparative Example 2: Based on Comparative Example 1, the amount of adhesive CMC-SBR was increased to 10%, and the other processes remained unchanged.
[0029] Comparative Example 3: Based on Example 1, the amount of the composite adhesive was increased to 10%, and the other processes remained unchanged.
[0030] Example 6: The commercially available LiPAA solution was replaced with the one prepared by the present invention, as follows: The preparation of the polyacrylic acid solution comprises the following steps: (1) adding acrylic acid to anhydrous ethanol, stirring evenly, adding 1,4,8,11-tetrakis(carbamoylmethyl)-1,4,8,11-tetraazacyclotetradecane and an activator (wherein the mass ratio of acrylic acid, 1,4,8,11-tetrakis(carbamoylmethyl)-1,4,8,11-tetraazacyclotetradecane and the activator is 1:1.7:2.7), stirring at 60-70° C. for 4-5 hours, purifying, evaporating and concentrating, and drying to obtain modified acrylic acid; (2) Add modified acrylic acid, lithium acrylate, and vinyl ethylene carbonate to methanol and stir evenly, add azobisisobutyronitrile (the mass ratio of modified acrylic acid, lithium acrylate, vinyl ethylene carbonate, and azobisisobutyronitrile is 1:7-8:0.4-0.5:0.08-0.1), introduce nitrogen and stir for 20-24 hours at 80-95°C, filter, wash, and dry to obtain lithium polyacrylate; (3) Add 4 g of lithium polyacrylate to 96 g of deionized water and stir evenly to obtain a LiPAA solution with a lithium polyacrylate content of 4%; The LiPAA solution, the xanthan gum solution, the sodium hyaluronate solution, and the styrene-butadiene rubber latex were mixed in a mass ratio of 4:4:1:1, and stirred at 350 r / min for 12 h to obtain a composite adhesive.
[0031] Example 7: Based on Example 6, the commercially available SBR emulsion was replaced with the one prepared by the present invention, as follows: The preparation method of the SBR emulsion comprises the following steps: (1) adding 33-35 parts of styrene-butadiene rubber to 95-100 parts of deionized water and stirring evenly, adding 8-12 parts of peracetic acid, stirring at 25-30° C. for 1-2 hours, purifying, washing, and drying to obtain epoxidized styrene-butadiene rubber; (2) adding 13-15 parts of epoxidized styrene-butadiene rubber into a reaction kettle and stirring evenly, adding 13-16 parts of 2,4-aminopyrimidine-5-carboxylic acid and 5-6 parts of trifluoroacetic acid, stirring at 80-90° C. for 1.5-2 h under microwave conditions of 200-250 W, and purifying to obtain active styrene-butadiene rubber; (3) adding 15-17 parts of active styrene-butadiene rubber into deionized water and stirring evenly, adding 8-10 parts of amino-tetraethylene glycol-carboxylic acid and 7-9 parts of activator, stirring at 50-60° C. for 7-8 hours, and obtaining modified styrene-butadiene rubber; (4) adding modified styrene-butadiene rubber and Tween 80 in a mass ratio of 4:0.4-0.5 into deionized water for ultrasonic dispersion and shear dispersion to obtain an SBR emulsion with an effective content of 48wt% (the effective substance is modified styrene-butadiene rubber); The LiPAA solution, xanthan gum solution, sodium hyaluronate solution and SBR emulsion were mixed in a mass ratio of 4:4:1:1, and stirred at 350 r / min for 12 h to obtain a composite adhesive.
[0032] Comparative Example 4: Based on Example 7, a commercially available LiPAA solution was used, and only the commercially available SBR emulsion was replaced with the one prepared by the present invention, as follows: The LiPAA solution, xanthan gum solution, sodium hyaluronate solution and SBR emulsion were mixed in a mass ratio of 4:4:1:1, and stirred at 350 r / min for 12 h to obtain a composite adhesive.
[0033] The performance test process is as follows: (1) Graphite, composite binder, and Super P are added to a ball mill at a mass ratio of 95:3:2, and ball milled at a speed of 150 r / min. At the same time, NMP is added in small amounts and multiple times until the mixture becomes viscous. Finally, ball milled at a speed of 200 r / min for 2 hours to obtain a slurry, which is coated on a copper foil and dried at 100°C for 24 hours to obtain a negative electrode sheet, ensuring that the average loading of active substances in the negative electrode sheet is 7 mg / cm2; the negative electrode sheet is cut into a circular electrode sheet with a diameter of 12 nm by a sheet punching machine. (2) Preparation of electrolyte: lithium hexafluorophosphate, fluoroethylene carbonate, and vinyl carbonate are added to diethyl carbonate, dimethyl carbonate, and vinyl carbonate in a volume ratio of 1:1:1, and mixed evenly to obtain an electrolyte, so that the concentration of lithium hexafluorophosphate is 1 mol / L, the content of fluoroethylene carbonate is 10%, and the content of vinyl carbonate is 2%. (3) Preparation of the battery: In an argon atmosphere, use a graphite electrode as the working electrode and a metal lithium sheet as the counter electrode to assemble the battery and let it stand for 12 h to obtain the battery to be tested.
[0034] (1) Mechanical properties test: The negative electrode sheet was cut into strips of 10 mm × 100 mm, and a 10 mm wide tape was pasted on the electrode sheet. The peel strength test was performed using a multifunctional tensile testing machine at a tensile speed of 100 mm / min. The negative electrode sheet was cut into strips of 50 mm × 15 mm, and the thickness was measured using a spiral micrometer. The tensile strength test was performed using a multifunctional tensile testing machine at a tensile speed of 20 mm / min. The experimental data are shown in Table 1.
[0035] (2) Electrochemical performance test: The Blue Power Battery Charge and Discharge Test System was used to conduct cycle and rate performance tests. The charge and discharge voltage range was set to 0.01–1.5 V. In the cycle performance test, the battery was cycled 150 times at current densities of 0.5 C and 2 C (1 C = 372 mA g−1). The experimental data are shown in Table 2.
[0036]
[0037]
[0038] Conclusion: As can be seen from Table 1, Example 1 and Example 4 have the best comprehensive performance, that is, the mass ratio of LiPAA solution, thickening solution, hyaluronic acid solution, and SBR emulsion is 4:4:1:1. Comparative Example 1 is a traditional binder CMC-SBR, and the tensile strength, peeling force and capacity retention rate are significantly weaker than those of Example 1, which shows that the composite binder based on lithium polyacrylate has good comprehensive performance, and in the binder ratio of the present invention, the mass ratio of SBR emulsion only accounts for 10% of the total binder, which means that only a small amount of SBR is needed to maintain the bonding force and integrity of the electrode, which also helps to improve the effectiveness of other substances compounded with the binder. At the same time, in order to verify the effect of the amount of binder added on the electrode, the present invention increases the amount of binder added to 10% based on Example 1 and Comparative Example 1, respectively. The results show that for the traditional binder CMC-SBR, the performance is slightly improved; while the binder prepared by the present invention has excellent properties, but the viscosity is too large, and the coating is difficult and has no use value, which can also confirm that the binder of the present invention has a small amount of high efficiency.
[0039] As can be seen from Table 2, in Example 6, the commercially available lithium polyacrylate is replaced by the one prepared by the present invention. Compared with the commercially available linear structure, the 1,4,8,11-tetrakis(carbamoylmethyl)-1,4,8,11-tetraazacyclotetradecane introduced by the present invention forms a branched structure during the polymerization process, which enhances the mechanical properties and tensile strength. The ethylene carbonate introduced by the copolymerization improves the wettability of the electrode and the electrolyte, reduces the resistance, and slightly improves the capacity retention rate; in Example 7, the commercially available SBR emulsion is further replaced by the one prepared by the present invention, and the multi-active functional groups promote the formation of intermolecular hydrogen bonds with the carboxyl groups in the polysaccharide and the lithium polyacrylate, which enhances the tensile strength and peeling force, and the introduced aqueous groups improve the dispersibility, and improve the overall mechanical properties and adhesion of the binder; compared with Example 7, Comparative Example 4 only replaces the SBR emulsion, and the mechanical properties are reduced, which corresponds to the data of Examples 6 and 7, that is, the LiPAA solution and SBR emulsion prepared by the present invention also have a good synergistic effect.
[0040] In summary, the present invention successfully provides a high-performance composite binder with good mechanical properties, strong adhesion and good ionic conductivity through a composite lithium polyacrylate aqueous binder, which can be used for the preparation of graphite negative electrodes.
[0041] Finally, it should be noted that the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art can still modify the technical solutions described in the aforementioned embodiments or replace some of the technical features therein by equivalents. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A method for preparing a high-performance composite binder for a graphite negative electrode, characterized in that: The following steps are involved: The LiPAA solution, the thickening solution, the sodium hyaluronate solution and the SBR emulsion are stirred and mixed to obtain a composite adhesive.
2. The method for preparing a high-performance composite binder for a graphite negative electrode according to claim 1, characterized in that: The composite binder comprises the following raw materials, calculated based on 100 parts by mass: 20 to 50 parts of LiPAA solution, 20 to 40 parts of thickening solution, 10 to 20 parts of sodium hyaluronate solution, and the rest is SBR emulsion.
3. The method for preparing a high-performance composite binder for a graphite negative electrode according to claim 1, characterized in that: The content of lithium polyacrylate in the LiPAA solution is 3.8-4.2wt%; the content of thickener in the thickener thickening solution is 1.8-2.2wt%; the content of sodium hyaluronate in the sodium hyaluronate solution is 1.8-2.2wt%; and the content of effective substances in the SBR emulsion is 46-50wt%.
4. The method for preparing a high-performance composite binder for a graphite negative electrode according to claim 1, characterized in that: The thickener in the thickening solution includes one of sodium carboxymethyl cellulose and xanthan gum; and the effective substance in the SBR emulsion is styrene-butadiene rubber.
5. The method for preparing a high-performance composite binder for a graphite negative electrode according to claim 1, characterized in that: During the stirring and mixing process, the rotation speed is 350-450 r / min and the time is 11-13 h.
6. The method for preparing a high-performance composite binder for a graphite negative electrode according to claim 1, characterized in that: The method for preparing lithium polyacrylate in the LiPAA solution comprises the following steps: (1) Add acrylic acid to anhydrous ethanol, stir evenly, add 1,4,8,11-tetrakis(carbamoylmethyl)-1,4,8,11-tetraazacyclotetradecane and an activator, stir at 60-70°C for 4-5 hours, purify, evaporate and concentrate, and dry to obtain modified acrylic acid; (2) Add modified acrylic acid, lithium acrylate and vinyl ethylene carbonate to methanol and stir evenly, add azobisisobutyronitrile, introduce nitrogen and stir at 80-95°C for 20-24 hours, filter, wash and dry to obtain lithium polyacrylate.
7. The method for preparing a high-performance composite binder for a graphite negative electrode according to claim 6, characterized in that: In the modified acrylic acid, the mass ratio of acrylic acid, 1,4,8,11-tetrakis(carbamoylmethyl)-1,4,8,11-tetraazacyclotetradecane and activator is 1:1.5-1.8:2.5-3; in the lithium polyacrylate, the mass ratio of modified acrylic acid, lithium acrylate, vinyl ethylene carbonate and azobisisobutyronitrile is 1:7-8:0.4-0.5:0.08-0.
1.
8. The method for preparing a high-performance composite binder for a graphite negative electrode according to claim 1, characterized in that: The preparation method of the SBR emulsion comprises the following steps: (1) adding styrene-butadiene rubber to deionized water and stirring evenly, adding peracetic acid, stirring at 25-30° C. for 1-2 hours, purifying, washing, and drying to obtain epoxidized styrene-butadiene rubber; (2) adding epoxidized styrene-butadiene rubber into a reaction kettle and stirring evenly, adding 2,4-aminopyrimidine-5-carboxylic acid and trifluoroacetic acid, stirring at 80-90° C. for 1.5-2 h under microwave conditions of 200-250 W, and purifying to obtain active styrene-butadiene rubber; (3) Adding active styrene-butadiene rubber to deionized water and stirring evenly, adding amino-tetraethylene glycol-carboxylic acid and an activator, stirring at 50-60° C. for 7-8 hours, and obtaining modified styrene-butadiene rubber; (4) Add modified styrene-butadiene rubber and Tween 80 into deionized water for ultrasonic dispersion and shear dispersion to obtain SBR emulsion.
9. The method for preparing a high-performance composite binder for a graphite negative electrode according to claim 8, characterized in that: The epoxidized styrene-butadiene rubber comprises the following raw materials in parts by weight: 33-35 parts of styrene-butadiene rubber, 95-100 parts of deionized water, and 8-12 parts of peracetic acid; The active styrene-butadiene rubber comprises the following raw materials in parts by weight: 13 to 15 parts of epoxidized styrene-butadiene rubber, 13 to 16 parts of 2,4-aminopyrimidine-5-carboxylic acid, and 5 to 6 parts of trifluoroacetic acid; The modified styrene-butadiene rubber comprises the following raw materials in parts by weight: 15 to 17 parts of active styrene-butadiene, 8 to 10 parts of amino-tetraethylene glycol-carboxylic acid, and 7 to 9 parts of an activator; In the SBR emulsion, the mass ratio of modified styrene-butadiene rubber to Tween 80 is 4:0.4-0.5.